2019
DOI: 10.1002/kjm2.12093
|View full text |Cite
|
Sign up to set email alerts
|

PSMD4 regulates the malignancy of esophageal cancer cells by suppressing endoplasmic reticulum stress

Abstract: Proteasome 26S subunit non‐ATPase 4 (PSMD4) is an important proteasome ubiquitin receptor and plays a key role in endoplasmic reticulum stress (ERS). However, the study of PSMD4 in esophageal cancer (EC) is relatively rare. Here, we found that the expression of PSMD4 was markedly enhanced in EC tissues and cell lines. The cell counting kit‐8 (CCK‐8) assay showed that overexpression of PSMD4 significantly enhanced Eca109 cell viability, while inhibition of PSMD4 reduced Eca109 cell viability. Knockdown of PSMD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Recent studies indicate that ERS plays a key role in tumor progression. The initiation of ERS signaling can induce apoptosis in esophageal cancer cells (16,17), which may represent a novel insight for the therapeutic intervention of esophageal cancer. Several studies have demonstrated the role of E2 treatment in enhancing ERS in a few tumors (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicate that ERS plays a key role in tumor progression. The initiation of ERS signaling can induce apoptosis in esophageal cancer cells (16,17), which may represent a novel insight for the therapeutic intervention of esophageal cancer. Several studies have demonstrated the role of E2 treatment in enhancing ERS in a few tumors (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…The ER chaperone protein BIP is a major regulatory factor of ER homeostasis and stress response (Li et al, 2016). Many factors can cause ER homeostasis to be disrupted, including bacterial infection (Ma et al, 2019). Studies have found that microbial infection can trigger ERS, and ERS-activating cells can regulate the expression and activation of ERS-related proapoptotic molecules, ultimately determining whether cells are adaptive or undergo apoptosis (Ma et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Many factors can cause ER homeostasis to be disrupted, including bacterial infection (Ma et al, 2019). Studies have found that microbial infection can trigger ERS, and ERS-activating cells can regulate the expression and activation of ERS-related proapoptotic molecules, ultimately determining whether cells are adaptive or undergo apoptosis (Ma et al, 2019). This response allows pro-inflammatory molecules to be released during the chronic inflammation of the CD, leading to damage to the colon cells, and thereby impairing the integrity of the epithelial barrier.…”
Section: Introductionmentioning
confidence: 99%
“…They can promote cell proliferation and cell cycle progression prognosis in breast cancer cell lines ( Oguro et al, 2015 ; Okumura et al, 2018 ; Fararjeh et al, 2019 ; Zhao et al, 2020 ). In esophageal cancer, upregulation of PSMD4 can reduce endoplasmic reticulum stress-induced cell apoptosis to promote tumor progression ( Ma et al, 2019 ). It was also reported that PSMD9 was correlated with recurrence after radiotherapy in cervical cancer and can predict radiotherapy benefits in breast cancer ( Langlands et al, 2014 ; Köster et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%